Design and Analysis of Self-tuned Nonlinear PID Controller for XY Table Ballscrew Drive System - Abdullah, Lokman; Jamaludin, Zamberi; Salleh, Mohd Rizal; Abu Bakar, Baharudin; Maslan, Mohd Nazmin; Tsung Heng, Chiew; RAFAN, NUR AIDAWATY (2013)
Positioning systems in machine tools lately insists for high accuracy and self adjusting mechanism to be implemented into the system in order to sustain against various disturbance forces. The disturbance forces are in the form of both cutting forces and friction forces. The aim of this paper is to propose a controller namely Nonlinear Proportional Integral Derivative (NPID) to control the position of the system. The tracking error will be compensated by the NPID controller.The tracking performance of NPID controller is compared with conventional PID controller. The degree of robustness of both controllers is quantified based on reduction in the amplitudes of cutting force harmonics using Fast Fourier Transform. It is obvious that the average tracking performance result of NPID controller outweigh the PID controller about 8 % to 40 % better. The finalize design of NPID controller do provide brighter prospect for machining application such as milling process. The execution of NPID controller will offer flexibility since the controller are an adaptive type of controller in which it can automatically adjust for better value of gain based on the error generated from the system. Finally, it is recommended that in order to improvise further the NPID controller, control designer could embedded any type of add on features like dead zone compensator and tracking differentiator into the controller to improve the tracking performance.